Laboratory Study on the Susceptibility of Locally Bread Wheat Cultivars to Infestation by Green Bug - Hussein, H.; AL-neami, K. (Iraqi Journal of Science, 2024)
Five bread wheat cultivars was selected namely, IPA99, Tamouz 2, Rasheed, Abu-ghraib And Iraq, were selected for susceptibility to green bug, Schizaphis graminum R.(Aphididae: Homoptera) infestation. Experiments done in under laboratory temperature 20±2C˚, humidity 65±5 % at 12h light. Results have indicated that IPA99 was highly preferred by in S. graminum and no significant of differences with Rasheed and Abu-ghraib, while Iraq and Tamouz2 came second. Although all wheat cultivars were infested by S. graminum except Iraq cultivar which showed some tolerance when exposed to three densities of 5, 10, ap plant during the time of test was 4 weeks. the development time of nymphs were 8, 8, 9, 9.3and 8.3 days for cultivars IPA99, Tamoz2, Iraq, Rasheed and Abu-ghraib respectively with no significant differences. Female longevity of this species was 30, 25, 37.7, 35.5 and 44 days when reared on Iraq, Tamouz2, Abu-ghraib, Rasheed and IPA99 cultivars respectively .The highest fecundity of S.graminum was 82.5 n v ual ∕ female on IPA99 an lowe t wa 48 n v ual ∕ female for Iraq cultivar